Conocimiento y prácticas de hábitos saludables en adultos y adultos mayores del Barrio Yanacocha, cantón Loja. - Carchi Poma, Andrea Paulina (2017)
This research has as purpose to establish the knowledge and practices of healthy habits of adults and older adults in Yanacocha neighborhood, Canton Loja. The type of study is descriptive and the method of data collection was the survey, with the instrument of 16 questions applied to 150 adults and older adults. The results obtained are mostly aged between 50-59 years (39.3%), farmers (41%), primary school (50.66%), a high percentage know that healthy habits (90%), the 100% of those who claim to know the subject refer to physical exercise and healthy eating are activities that are performed as healthy habits. The 70% of the surveyed performed physical activity with a frequency of 1-2 times per week (68.8%) over a period of 30-45 minutes (62.7%). The activity that they practice more is walk (97.1%). Referring to the nutrition 61.33% consume fast food rarely, 43.3% consume fruit daily, protein consumption 64.6% responded that it made 1-2 times per week; 20.6% consume fiber frequently 3-4 times per week, the intake of soft drinks is made weekly (36%). KEY WORDS: adult, healthy habits, physical exercise, nutrition